(untitled) (Physical Education, Health and Social Sciences, 2026)
The wildlife–livestock interface (WLI) serves as a critical hotspot for zoonotic spillover of emerging viral pathogens, facilitating the transmission of viruses from wildlife reservoirs to livestock (as intermediate or bridge hosts) and subsequently to humans. This review synthesizes the multi-scale mechanisms underpinning viral spillover, including ecological drivers (such as habitat fragmentation, deforestation, intensive farming, wildlife trade, and climate change), genetic plasticity of RNA viruses (high mutation rates, quasi-species diversity, and recombination), cellular compatibility (receptor usage and tissue tropism), and viral evasion of innate immune responses (interferon antagonism via proteins like NS1, V, VP35). Special emphasis is placed on how livestock act as amplification or mixing vessels, enabling adaptation before human infection. Key case studies illustrate these processes: Henipaviruses (Nipah and Hendra viruses) demonstrate bat-to-pig/horse-to-human pathways or direct bat-to-human routes influenced by strain-specific pathogenesis and cultural practices; MERS-CoV highlights source-sink dynamics in dromedary camels with seasonal spillover linked to calving cycles. The document also explores the debated biodiversity-disease relationship (dilution vs. amplification effects), network ecology for identifying bridge hosts (rodents in human-dominated landscapes), and anthropogenic factors amplifying risk. Effective mitigation requires a One Health approach integrating surveillance in biodiversity hotspots, biosecurity at interfaces, predictive AI modeling, and global data sharing to anticipate and prevent future spillovers of viruses with pandemic potential.